Duration of Oral Anticoagulant Treatment in Patients with Venous Thromboembolism and a Deficiency of Antithrombin, Protein C or Protein S - A Decision Analysis - van den Belt, Angelique G. M.; Hutten, Barbara A.; Prins, Martin H.; Bossuyt, Patrick M. M. (Thrombosis and Haemostasis, 2000)
Patients with a first venous thromboembolic event and a deficiency of the coagulation inhibitors antithrombin, protein C or protein S have an increased risk of recurrent venous thromboembolism compared to patients without such a deficiency. A decision analysis was performed to assess the effect of continuing treatment with vitamin K antagonists on mortality by a reduction in fatal recurrent pulmonary embolism and an induction of fatal haemorrhages associated with their use. The treatment decision involves continuation or discontinuation of vitamin K antagonists in patients with a first spontaneous or secondary venous thromboembolism and an antithrombin, protein C or S deficiency. Although the efficiency of oral anticoagulation is high in all age groups early after the first thromboembolic event, it decreases over time. Our analysis indicates that the optimal treatment duration will vary, depending on the type of the initial event (spontaneous or secondary; deep venous thrombosis or pulmonary embolism), age, and time passed since the initial thromboembolic episode. Moreover, life-long duration of the prophylaxis seems not warranted in all patients.
Keywords: Secondary prevention; duration of treatment; vitamin K antagonists; thrombophilia